Enhancing Geriatric Assessment in Cancer Rehabilitation: Suggestions for Future Research - Su, Qing; Zeng, Xiaofeng (Journal of the American Geriatrics Society (JAGS), 2025)
See the related letter to the editor by Mohile et al. in this issue.